The Five-Factor Model plus Dominance in Chimpanzee Personality - James E. King; Aurelio José Figueredo (Journal of Research in Personality, 1997)
Forty-three trait-descriptive adjectives with representative items from the human Big-Five model were used to assess the factor structure of personality in 100 zoo chimpanzees. Interrater reliabilities were acceptably high, with an overall η of .75 and those of individual adjectives ranging from .55 to .81. Analysis of variance showed no significant interaction between zoos and individual trait descriptors or between zoos and factors based on those adjectives. There were therefore no between-zoo differences in patterns of intercorrelation among trait descriptors or among factors. Factor analysis showed that the chimpanzee ratings were accurately described by six factors, five of which resembled the human Big Five. The sixth factor was dominance related and was consistent with the central role of dominance in chimpanzee personality. Convergent and discriminant validity of the factor structure was excellent. These results are the first quantitative evidence of profound similarities in the personality structure of humans and chimpanzees.